Development of Chili Sauce from Pineapple and Banana Fortified with Eggshell Calcium - Teangpook*, Chowladda; Kongsombat, Panita; Matum, Maneeploy; Nuntachai, Nunchanok (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
Sauce is a popular condiment product. Thailand is a good source of pineapples and bananas, which are high in nutrients. Eggshell is also a source of calcium. This research developed a sauce from pineapple var. Phu Lae mixed with ripened banana var. Nam Wah and supplemented with calcium from eggshells. The suitable quantities of pineapple, banana and pineapple peel and core extract were studied based on a mixture design. The physical and chemical properties, sensory evaluation, three suitable calcium levels (0, 2, and 4%) and two pasteurization temperature levels (80-85ºC and 90-95ºC) were studied. Response surface methodology was applied and showed that all 3 components had significant effects on the sauce quality at the 0.05 level. The optimum product comprised 25.27% pineapple, 0.87% banana, 13.86% pineapple peel and core extract, 16% pickled red chili peppers, 11% pickled garlic bulbs, 26% sucrose, 2% salt, 1% vinegar, 2.12% water, and 1.88% calcium from the powdered eggshell. The product had an orange color, a pH of 4.20, and 1.61% acidity. This sauce was high in nutrients: 41.03% carbohydrate, 14.90% protein, 1.98% fat, 0.453% eggshell calcium, and 14.03 mg/kg total vitamin C. The antioxidant activity was 22.94 mg ascorbic acid/g. The optimum pasteurization temperature was 80-85ºC for 15 min. The sauce was moderately liked by panelists and has the potential to be processed into a low-cost commercial condiment. Keywords: sauce; pineapple; banana; egg shell calcium; mixture design *Corresponding author: E-mail: ifrcdt@ku.ac.th